Inactivation of Poliovirus Type 1 by the Kelly-Purdy Ultraviolet Seawater Treatment Unit - Hill, William F. (1969)
Three experiments were conducted to determine the effect of ultraviolet (UV) radiation on poliovirus-contaminated seawater. In two of the experiments, the effectiveness of the Kelly-Purdy UV Seawater Treatment Unit to inactivate poliovirus type 1 (T(1)) suspended in continuously flowing seawater was determined. In experiment 1, the observed survival ratio of poliovirus T(1) was 2.3 × 10(-4) (99.98% reduction) in 15.7 sec. No virus was detected (<0.2 plaque-forming unit/ml) in 20.6 seconds. The calculated half-life value was 1.29 sec. In experiment 2, the observed survival ratio of poliovirus T(1) was 5.9 × 10(-4) (99.94% reduction) in 11.7 sec. No virus was detected in 15.7 sec. The calculated half-life value was 1.37 sec. In experiment 3, a laboratory-controlled UV experiment designed to closely simulate the geometry of the continuously flowing seawater system, the observed survival ratios of poliovirus T(1) were 9.7 × 10(-3) (99.03% reduction) and 3.6 × 10(-4) (99.96% reduction) in 15 and 30 sec, respectively; the calculated half-life value was 2.38 sec. A statistically significant difference was found between the inactivation rates of poliovirus T(1) in the two test systems. This rate difference was attributed primarily to UV dosage and stirring effects. The data indicated that UV radiation effectively inactivated poliovirus T(1) in flowing seawater. These results validate the efficacy of the Kelly-Purdy UV Seawater Treatment Unit for use in commercial depuration systems.